2023
DOI: 10.1002/aenm.202203062
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Crossover Accelerates Degradation of Lithium Electrode in High Energy Density Rechargeable Lithium–Oxygen Batteries

Abstract: Lithium‐oxygen batteries (LOBs) are promising next‐generation rechargeable battery candidates due to theoretical energy densities that exceed those of conventional lithium‐ion batteries. Although LOB with high cell level energy density has been demonstrated under lean electrolyte and high areal capacity conditions, their cycle life is still poor, and the cell degradation mechanism remains unclear. In the present study, by use of a three‐electrode electrochemical setup and in situ MS analytical techniques, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Recently, our study using a three-electrode experimental setup revealed that these features originate from the change of reaction profile of the negative lithium electrode, not from the positive oxygen electrode. 5 In addition, it was also demonstrated that chemical crossover from the positive to negative electrode results in such a complicated reaction profile at the negative lithium electrode. 5 Actually, such a unique feature in the voltage profile of the discharge/charge cycle was also observed in the LOB cell operated at 2 mA h cm −2 (blue, red and black arrows in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our study using a three-electrode experimental setup revealed that these features originate from the change of reaction profile of the negative lithium electrode, not from the positive oxygen electrode. 5 In addition, it was also demonstrated that chemical crossover from the positive to negative electrode results in such a complicated reaction profile at the negative lithium electrode. 5 Actually, such a unique feature in the voltage profile of the discharge/charge cycle was also observed in the LOB cell operated at 2 mA h cm −2 (blue, red and black arrows in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on the design of practical LOB cells revealed the importance of the ratio of electrolyte amount against areal capacity (E/C, g A −1 h −1 ) for determining the performance of LOBs. [3][4][5] The E/C value has been used as an empirical parameter representing the electrolyte amount when studying lithium-ion battery (LIB) compounds. However, a recent study on lithium-metal-based rechargeable batteries demonstrated that E/C is a crucial parameter for performance evaluation in practical cell design conditions (i.e., lean electrolyte conditions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further improve the cycle performance, a solid electrolyte (lithium‐ion conducting glass‐ceramics, LICGC, Ohara) was introduced into the battery to inhibit the shuttle effect, wherein the byproducts formed at the cathode migrate to the Li anode and induce its deterioration. [ 37 ] Consequently, stable cycling up to 30 cycles is achieved (Figure 5d), which is one of the best cycle performances using a current density of 0.4 mA cm −2 and large limited capacity of 4.0 mAh cm −2 . [ 17a,19a,27b,c ] The stable cycling performance (19 cycles) of the Li–O 2 battery based on the solid electrolyte and the 552‐electrolyte also proves the stability of the GMS‐sheet (Figure S28, Supporting Information), and the major cause of battery death is not the GMS‐sheet cathode but other battery components, including the electrolyte and anode.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies are limited to the LiFSI/ether-based electrolyte system. In addition, except for several studies, , in most of the LOB studies, the performance evaluation of LOB has only been conducted at relatively low areal capacity and current density conditions. Thus, the practicality of this class of electrolytes for application in LOB remains unexplored.…”
Section: Introductionmentioning
confidence: 99%